Pemanfaatan Kulit Kayu Akasia (Acacia mangium Willd) untuk Papan Partikel dengan Kadar Fenol Formaldehida Rendah Utilization of Acacia (Acacia mangium Willd) Bark for Particleboard with Low Phenol Formaldehyde Content - Subyakto Subyakto; Lisman Suryanegara; Mohamad Gopar; Kurnia Wiji Prasetyo (Masyarakat Peneliti Kayu Indonesia, 2005)
Industrial forest plantation is a future for supplying raw material of wood industries. From the wood harvesting, bark wastes are abundantly resulted. As an illustration, a pulp factory in Palembang produces about 500 ton per day of bark waste of Acacia mangium Willd. At present the utilization of bark wastes was not optimally done. The purpose of this experiment was to utilize bark waste for particleboard, it is expected that high tannin content in the bark will reduce amount of adhesive applied.Fresh bark was cut into chips and processed further with a ring flaker machine to produce bark particles. Bark particles were mixed with Phenol Formaldehyde adhesive and water then hot pressed at temperature of 150ºC, pressure of 20 kgf/cm2, for 15 minutes. Amount of adhesive was varied at 4%, 6% and 8% based on dry weight of particles. Water was added for 10% of dry weight of particles. The size of board was 25 cm x 25 cm x 1 cm, with target densities of 0.7 and 0.9 g/cm3, with 2 replications. Boards were tested for their physical and mechanical properties in accordance with JIS A 5908.Results shown that board with density of 0.9 g/cm3 and amount of adhesive of 6% and 8% have internal bond and MOR (modulus of rupture) that met JIS A5908 type 8; while values of MOE (modulus of elasticity) and thickness swelling were not met the standard